Risk of malnutrition and zinc deficiency in community-living elderly men and women: the Tromsø Study - Kvamme, Jan-Magnus; Grønli, Ole Kristian; Jacobsen, Bjarne Koster; Florholmen, Jon (Public Health Nutrition, 2014)
Early view